An electronic companion to microbiology for majors - kathleen campbell smith; Smith, Kathleen Campbell; Katz, Diana Sue.; Cogito Learning Media, Inc. (New York : Cogito Learning Media, Inc., 1998)
Multimedia study guide for microbiology which includes interactive review and self-testing of key concepts; interactive multiple choice, "drag and drop," true/false, and fill-in-the-blank questions; accompanying workbook with focused summaries and additional problems and exercises. Uses concise text, animation and video.
Title from disc label.
Workbook by Kathleen Campbell Smith, additional questions by Diana Sue Katz.
System requirements (Windows): IBM PC or compatibles; Windows 3.1 or higher; 486 processor or higher; 8MB RAM or more (for Windows 95, requires 12MB or more RAM).
System requirements (Macintosh): Macintosh with 040 processor or higher; System 7.1 or later; 8MB or more RAM (12MB or more RAM required with PowerPC).
Keywords: Microbiology -- Software; Microbiology -- Examinations, questions, etc. -- Software; Microbiology -- examination questions -- CD-ROM.; Microbiology -- outlines -- CD-ROM.